Putative Nociceptive Responses in a Decapod Crustacean: The Shore Crab (Carcinus maenas) - Eleftherios Kasiouras; Peter C. Hubbard; Albin Gräns; Lynne U. Sneddon (Biology)
Nociceptors are receptors that detect injurious stimuli and are necessary to convey such information from the periphery to the central nervous system. While nociception has been extensively studied in various taxa, there is relatively little electrophysiological evidence for the existence of nociceptors in decapod crustaceans. This study investigated putative nociceptive responses in the shore crabs, specifically their response to mechanical and noxious chemical stimuli. Extracellular multi-unit electrophysiological recordings were conducted from the anterior ganglion and the circumesophageal connective ganglia to assess nociceptive responses. Soft tissues at the joints of the chelae, antennae, and walking legs were stimulated using acetic acid (noxious stimulus) and von Frey hairs (mechanical stimulus), while nearby ganglion activity was recorded. The results indicate the existence of nociceptors in the tested areas, with mechanical stimuli eliciting shorter, more intense neural activity compared with acetic acid. Although acetic acid triggered responses in all areas, the antennae and antennules did not respond to mechanical stimuli. Though we acknowledge the challenges of conducting in vivo electrophysiological recordings, future research should focus on further characterizing nociceptor activity because the results suggest the presence of nociceptors.